Inveterate apical periodontitis comprehensive treatment technology (Эндодонтия Today, 2020)
The paper presents an original method of complex therapy in the treatment of chronic apical periodontitis in the acute stage with the use of preparations of calcilan and polyoxidonium. There are the data of bacteriological examination of exudate root canals, immunological study of oral fluid. 62 patients aged 25-35 years with a diagnosis of chronic apical periodontitis in the acute stage were treated. Patients were divided into 2 groups: the first group of 30 patients received standard therapy, in the treatment of 32 patients of the second group an additional consumption of calcilan and polyoxidonium was administered. A control group consisted of 10 healthy subjects. The results of clinical and laboratory studies have proved the effectiveness of the combined use of calcilan and polyoxidonium in treatment of chronic apical periodontitis in the acute stage